Impact of the Band‐Edge Fine Structure on the Energy Transfer between Colloidal Quantum Dots. Issue 2 (27th November 2013) - Moreels, Iwan; Justo, Yolanda; Rainò, Gabriele; Stöferle, Thilo; Hens, Zeger; Mahrt, Rainer F.
<x xml:space="preserve">Abstract</x> Förster energy transfer plays an important role in spectroscopic rulers, photovoltaics and solid‐state light emission, and here is a novel way of controlling it. Using a colloidal quantum dot bilayer system, it is possible to change the transfer rate while maintaining a constant efficiency. The key is a thermal exciton redistribution over the different band‐edge states, varying both the Förster and the intrinsic emission rate simultaneously. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>